Strategi Dakwah DKM Dalam Memakmurkan Masjid Al-Imam Asy-Syafi’i Kecamatan Seberang Ulu II Kota Palembang - Dinda Permatasari; Hidayat Hidayat (Social Science and Contemporary Issues Journal, 2024)
This thesis is entitled "Da'wah Strategy DKM in Prospering the Al-Imam Asy-Syafi'i Mosque, Kecamatan Seberang Ulu II, Kota Palembang". The purpose of this research is to determine the da'wah strategy used by the DKM (Mosque Prosperity Council) and to determine the supporting and inhibiting factors in the prosperity of the Al-Imam Asy-Syafi'i mosque, Seberang Ulu II District, Palembang City. This type of research is field research with a qualitative approach. There are two data sources used, namely primary and secondary data sources. Data collection techniques through observation, interviews and documentation. The location of this research is Jl. Ki Anwar Mangku Lr. Asli, Kecamatan Seberang Ulu II, Kelurahan Sentosa, Kota Palembang. According to Miles and Huberman, the data analysis technique used is in three stages, namely data reduction, data display, conclusion drawing/verification. The results of this research are to find out the da'wah strategy used, namely by softening people's hearts by always mingling with noble morals and providing assistance such as in the distribution of zakat and sacrificial meat, and also da'wah which is carried out scientifically by understanding the Al-Qur'an and Al- hadith with the understanding of the blessed generation, namely the friends or with scientific study activities held by DKM, as well as by holding corpse training practices or the Dauroh and Tahsin programs. Then, the inhibiting factor in the prosperity of the Al-Imam Asy-Syafi'i mosque is that there are still people who do not fully support the activities at the Imam Asy-Syafi'i mosque. Meanwhile, the supporting factors are the enthusiasm of the congregation in participating in the recitation and supporting all activities including the congregation outside the mosque environment, good coordination between the congregation and DKM, adequate human resources, and good management.